INVENTARISASI KEANEKARAGAMAN TUMBUHAN LUMUT (Bryophyta) PADA HABITAT ALIRAN SUNGAI DAN HUTAN WAITATIRI, AMBON - Pradana, Sendy Putra; Tuapattinaya, Prelly Marsell Jolanda; Latupeirissa, Louvenska Nona; Pattiasina, Eifan Boyke (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
Background: Bryophytes (Bryophyta) are small terrestrial plants that are generally green in color. This study aims to identify the types of bryophytes (Bryophyta) and classify their presence on various substrates around the Waitatiri River and forest, Ambon. Methods: The study was conducted along the Waitatiri River, Ambon, using the exploratory survey method. Data were collected through direct observation of bryophyte species in the field. Results: The results revealed various types of bryophytes, including liverworts (Marchantiophyta) and mosses (Bryopsida). Identified species included Rhizomnium punctatum, Dicranum scoparium, Spahgnum fimbriatum, Polytrichum juniperinum, Marchantia polymorpha, and Metzgeria furcata.. The highest distribution was found on rocky substrates with two dominant species, while the lowest distribution was observed on tree bark. Conclusion: This study highlights the variation in Bryophyta species distributed on rocky substrates and tree bark within the Waitatiri ecosystem, Ambon, with the largest species distribution found on rocky substrates.